Evaluation of Reaction Time on Karate Athletes UKM Syiah Kuala University - Syamsulrizal, Syamsulrizal; Riski Afrianda, Tengku; Iqbal, Muhammad; Marlina, Yeni; Zahara, Zahara (INSPIREE: Indonesian Sport Innovation Review, 2022)
The  purpose  of  the study. Reaction time is a determining factor in sports, especially in martial arts. The purpose of this study is to evaluate the reaction time of UKM Karate athletes at Syiah Kuala University. Materials and methods. The approach in this study uses a quantitative approach. The sampling technique used purposive sampling, which means this technique is used to achieve certain goals. The samples in this study were athletes from UKM karate at Syiah Kuala University. The data collection technique was carried out by using the whole body reaction test to measure the reaction time of the athlete's arms and legs. Results. results of the research in the form of a whole body reaction test, the results using the formula for the average value and the total percentage can be concluded: (1) The arm reaction time test with the total average value for male athletes is 0.169 seconds and female athletes are 0.173, and the highest percentage is in the very good category, amounting to 87% for male and female athletes, 75% in the very good category and (2) the limb reaction time test has an average value of 0.269 seconds for male athletes and female athletes of 0.361 seconds, with the highest percentage value amounted to 100% in the good category for male athletes and for female athletes it was in the sufficient category with a percentage of 50%. Conclusions. the analysis show that most athletes have been able to maintain and increase reaction time well, to be able to improve and maintain it, regular and continuous training is needed